Determine Most Stable Isobar for Nuclides with A= (15-30) & (101- 115) - S. Nayyef, Murtadha; T. Jaralla, Naz (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
In this study the most stable isobar for some isobaric families (light and  intermediate ) nuclei with mass number (A) equals to (15-30) & (101- 115) have been determined. This determination of stable nuclide can help to determine the suitable nuclide, which can be used in different fields.Most stable isobar can be determined by two means. First: plot mass parabolas (plotting the binding energy (B.E) as a function of the atomic number (Z)) for these isobaric families, in this method most stable isobars represent the lowest point in mass parabola (the nuclide with the highest value of binding energy).Second: calculated the atomic number for most stable isobar (ZA) value.Our results show that there is only one stable nuclide for isobars with odd mass number (A) (one mass parabolas), while for nuclides with an even mass number (A) there is more than one stable nuclide (two mass parabola).Also, our results show that nuclides representing the most stable isobars in the two methods, which used in this study practically, are the same nuclide.